2022
DOI: 10.3390/nu14020343
|View full text |Cite
|
Sign up to set email alerts
|

Association between Levocarnitine Treatment and the Change in Knee Extensor Strength in Patients Undergoing Hemodialysis: A Post-Hoc Analysis of the Osaka Dialysis Complication Study (ODCS)

Abstract: Carnitine deficiency is prevalent in patients undergoing hemodialysis, and it could result in lowered muscle strength. So far, the effect of treatment with levocarnitine on lower limb muscle strength has not been well described. This observational study examined the association between treatment with levocarnitine with the change in knee extensor strength (KES) in hemodialysis patients. Eligible patients were selected from the participants enrolled in a prospective cohort study for whom muscle strength was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Although some have suggested that dialysis patients should be routinely evaluated for frailty, 18 the utility of this approach is uncertain given the lack of proven interventions. Candidate therapies, such as exercise training, 19 androgen supplementation, 20 carnitine administration, 21 and perhaps other forms of nutritional support. 22 The high prevalence of frailty, the high associated costs, 23 and the excess risk of associated adverse outcomes indicate the need for clinical trials to identify effective treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Although some have suggested that dialysis patients should be routinely evaluated for frailty, 18 the utility of this approach is uncertain given the lack of proven interventions. Candidate therapies, such as exercise training, 19 androgen supplementation, 20 carnitine administration, 21 and perhaps other forms of nutritional support. 22 The high prevalence of frailty, the high associated costs, 23 and the excess risk of associated adverse outcomes indicate the need for clinical trials to identify effective treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle strengths were expressed in the unit of kilogram force (kgf). Hip abduction strength and knee extension strength were standardized for body size by dividing them by body weight (in kilogram) after haemodialysis (“dry weight”) 25 …”
Section: Methodsmentioning
confidence: 99%